Serum Immunoglobulins level in Bangladeshi Dockyard Labourers - Sayeed, Muhammad Shahdaat Bin; Al Maruf, Abdullah; Basher, Amitouzea; Huda, Naimul; Toufique, Syeda Amina; Hasnat, Abul (Dhaka University Journal of Pharmaceutical Sciences, 2011)
The purpose of the study was to evaluate the serum level of immunoglobulins in Bangladeshi dockyard labourers compared to healthy day labourers. One hundred dockyard labourers, age ranging from 19 to 42 years, were randomly recruited from different dockyards of Keranigonj, Dhaka, Bangladesh. The control group included 100 day labourers matched by age, sex and socio-economic status to that of dockyard labourers who were not exposed to environmental hazards of dockyard. Blood samples were analyzed for determining the serum levels of immunoglobulin (IgG, IgA & IgM) by turbidimetry method using an immunoglobulin kit. The serum concentration of IgA & IgG were found to be decreased, whereas that of IgM increased in dockyard labourers as compared to control group, but the differences were not significant (p>0.05). No significant relationship was found between the socio-demographic variables and immunoglobulin levels at 5% level of significance. But study with larger number of population is required for further evaluation of the relationship between the immune status and health hazards to confirm these findings. Key words: Dockyard labourers; Occupational exposure; Immunoglobulin. DOI: http://dx.doi.org/10.3329/dujps.v9i2.7885 Dhaka Univ. J. Pharm. Sci. 9(2): 91-95, 2010 (December)